Tomato Hornworm Manduca quinquemaculata (Haworth) (Insecta: Lepidoptera: Sphingidae) - Morgan A. Byron; Jennifer Lynn Gillett-Kaufman (EDIS)
The tomato hornworm, Manduca quinquemaculata (Haworth), is a common garden pest that feeds on plants in the Solanaceae (nightshade) family including tomato, peppers, eggplant, and potato. https://edis.ifas.ufl.edu/in1206